Evolution of phyllospheric microorganisms on Vitis vinifera L. cvs. Pinot noir and Chardonnay - Africa, Amber Justine (Stellenbosch : Stellenbosch University, 2023)
Thesis (MSc)--Stellenbosch University, 2023.